2020
DOI: 10.3390/agronomy10081142
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inoculation of Rhizobacteria and Biochar Application Improves Growth and Nutrientsin Soybean and Enriches Soil Nutrients and Enzymes

Abstract: Gradual depletion in soil nutrients has affected soil fertility, soil nutrients, and the activities of soil enzymes. The applications of multifarious rhizobacteria can help to overcome these issues, however, the effect of co-inoculation of plant-growth promoting rhizobacteria (PGPR) and biochar on growth andnutrient levelsin soybean and on the level of soil nutrients and enzymes needs in-depth study. The present study aimed to evaluate the effect of co-inoculation of multifarious Bradyrhizobium japonicum USDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…Considering their ability in crop improvement, they are used as a substitute for chemical application in agriculture. Most of the rhizosphere bacteria secrete secondary metabolites called siderophores which act as chelating agents for ferric iron, produced under low iron stress [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Considering their ability in crop improvement, they are used as a substitute for chemical application in agriculture. Most of the rhizosphere bacteria secrete secondary metabolites called siderophores which act as chelating agents for ferric iron, produced under low iron stress [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Soil salinity is an increasing problem worldwide for about 27% of the world’s arable land [ 6 ]. Plant growth in these soils is adversely affected by both excess salts and excess sodium levels [ 7 ]. Saline soil prevents the normal growth of crops and results in poor crop yield [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth in these soils is adversely affected by both excess salts and excess sodium levels [ 7 ]. Saline soil prevents the normal growth of crops and results in poor crop yield [ 7 ]. The effects of soil salinization are more detrimental, particularly in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPK + BZnFe (100:75:75:3:6:6 kg/ha) treatment significantly increased active P content by 40%, total P content by 38% and total K content by 22% in comparison to the control without mineral fertiliser. Several other authors also reported the nutrient contents in the soil before and after plant cultivation [ 39 , 40 ]. Some other studies about poultry manure showed limitations so that NPK alone or with a combination of other nutrient fertilisers could increase the essential macronutrients in soil [ 41 ].…”
Section: Resultsmentioning
confidence: 99%